A Narrative Inquiry into EFL Teachers’ Emotional Geographies in Online Grammar ‘Funtainment’ Assessment - Sujiatmoko, Ahmad Heki; Setyowati, Lestari; MR, Elvira Rasyida; Ubaidillah, M. Faruq; Namaziandost, Ehsan (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
In EFL classrooms, each teacher is expected to be able to act professionally in teaching and assessing the students through the ability to control emotions. However, studies that capture such phenomenon are lacking. This study investigated the narratives of Indonesian EFL teachers’ emotional geographies who conducted online assessments using 'Funtainment Assessment' in 'Grammar' classes. The study employed a narrative inquiry as the design by collecting individual in-depth interview data over four months. Findings unveiled five aspects that influenced changes in the participants' emotional geographies: physical, moral, sociocultural, professional, and political. Participants had a variety of attitudes in response to the emotions that arose when assessing the students' grammar competence online. Interestingly, the participants experienced continuous adaptation to the practice of negotiation to the emotional changes Thus, it did not distract the professional developments they had done through agentive actions. The study's empirical results also suggest that the 'emotional geography dimensions' contributed to future teachers' professional developme